Pengaruh Penempatan Kerja, Disiplin Kerja dan Pemanfaatan Teknologi Informasi terhadap Kinerja - Muslim, Muslim; Bachtiar, Yanuar; Daud, Ibrahim; Firdausi, Iqbal; Husien, Nirza Mazuki (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) IBE Indonesia, 2024)
This study aims to determine the effect of work placement, work discipline and the use of information technology on the performance of employees of the Regional Secretariat of Tanah Laut Regency. The research method is an explanatory research. The population in this study were 104 civil servants of Tanah Laut Regency. All members are used as a sample which is called saturated sampling or census. So the number of samples in this study were 104 people. Data analysis technique with multiple linear regression analysis using the SPSS for windows program. The results of the study show that work placement has an effect on the performance of the employees of the Regional Secretariat of Tanah Laut Regency. Work discipline affects the performance of the employees. Utilization of work information technology affects the performance of employees. Work placement, work discipline and utilization of information technology simultaneously affect the performance of the employees.